Antibiotic susceptibility of Staphylococcus epidermidis among undergraduate students in Malaysia Public University Health Campus - Abu Zarrin AM,; Nor Munirah MA,; Mohammad Izwan EO,; Abdullah AS,; Hanani Ahmad Yusof @ Hanafi, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Staphylococcus epidermidis (S. epidermidis) has become one of the major concerns in the hospital setting due to its ability to cause hospital-acquired infection particularly from medical device contamination. The management of S. epidermidis infections become more challenging with the increase of antimicrobial resistance cases over the past years. Limited reports on S. epidermidis antibiotic resistance among healthy people leave uncertainty about the magnitude of antimicrobial resistance spreads among the community. Therefore, this study aimed to identify the antibiotic susceptibility pattern of S. epidermidis isolated from healthy undergraduate students in one of Malaysia public universities-health campuses. Ninety-six hand palm swab samples were collected and undergo several tests, including microscopic, biochemical identification tests and antibiotic susceptibility test for erythromycin, oxacillin, gentamicin, penicillin and tetracycline following Kirby-Bauer test. A total of 43 samples showed the presence of S. epidermidis (44.8%), where 72.1% of the isolates showed resistance towards at least one type of antibiotic. The highest and lowest resistance was observed for penicillin and gentamycin, respectively. Although there is no significant difference of antibiotic susceptibility pattern was observed between genders, the presence of high antibiotic resistance in S. epidermidis among these healthy communities should warrant further investigation since the spreading of the resistant strain could occur in the wider community population without notice.